Late sigillata from fish-salting Workshop 1 In Tróia (Portugal) - Patrícia Magalhães, Ana (Rei Cretariae Romanae Fautorum Acta, 2012)
Recently, as part of my master thesis at the University of Lisbon, I have been studying the field reports and the ceramics, in particular the terra sigillata, from the first excavations of workshop 1 in tróia, Portugal, one of the largest Roman fish-salting production centres known. although some of the information registered during these excavations was lost, some field reports and letters exchanged by the investigators were preserved and are worth an attentive study, besides allowing the interpretation of an impressive volume of ceramics deposited in the national museum of archaeology in Lisbon (Portugal), which may enrich the knowledge of the workshop they came from.